Disciplinary Power Lying Behind the Requisite of English Language Mastery in International Scholarships - Alber Josué Forero-Mondragón; Álvaro Hernán Quintero-Polo (Universidad Nacional de Colombia, 2022)
This article reports a study about how the discourse of standard English exercises disciplinary power in five international scholarships programs. This research interest arises from problematizing the discourse of standard English present in the requisite of proficiency certification through so-called valid tests. Adapting Fairclough's critical discourse analysis model, we analyzed a corpus of five scholarship calls for applications open from 2011 to 2014. Findings reveal that the discourse of standard English entangles with the discourses of globalization, education quality, and competitiveness and qualifications to serve as the path to the construction of the subjects' scholarship applicants. In this entanglement, school is set as a breeding ground whose disciplinary techniques (e.g., test training) objectivize people to satisfy multinational corporations' hiring processes.